Potencial energético do bagaço e palhiço de cana-de-açúcar, cv. SP80-1842, em área de alambique artesanal - Viana, Laryssa Ferreira (2011)
The present work was conducted with the objective of evaluate the energetic potential of the sugar-cane bagasse and chaff, produced by an artisan distillery, carachteristical to small cachaça producers in Minas Gerais, during harvest season of the sugar cane, from June to October, cicle of the rattoon, harvested without prior burning of the crop. It was utilized the variety SP80-1842 which presents a good agricultural productivity in plant-cane and rattoon. The experiment was held in the area of distillery João Mendes - "JM", in Perdões, Minas Gerais in the agricultural year of 2008/2009. The treatments were evaluated utilizing the experimental design consisted of ramdomized blocks, with 5 treatments , corresponding to 5 cutting times (June, July, August, September and October), with 5 repetitions, totalizing 25 parcels, being the data taken in the three central lines. The evaluated characters were: the yield of the whole cane, yield of the culm, yield of the chaff, yield of the bagasse, yield of the bagasse + chaff, brix (%) juice, yield of the dry matter of the chaff and of the bagasse and elementar analysis of the material. It was made variance analysis with the aid of the use of computer system Sisvar®. The yield of the bagasse was higher in September, probably this is due to peak of drougt time in the region.The values obtained for the brix were higher in August/September/October due to the a greater maturation of the sugar-cane. It was verified that the superior calorific power and yield in calories of the bagasse and chaff was higher in the months of September/October than in the months of June/July/August, probably this is due to less moisture contents and higher yield in dry matter in September/October. For the moisture in dry base there is a bigger variation present in the bagasse and, in general, the lower the moisture the higher the calorific power is. The Inferior Calorific Power, The Useful Calorific Power and the Yield in calories of the bagasse and chaff increased with the progress of the harvest season of the sugar cane.